Hydroponic Training as an Effort to Improve Food Security, Community Economy, and Environmental Quality in the City of Surakarta - Yonathan Suryo Pambudi; Richardus Indra Gunawan; Elvis Umbu Lolo; Cicik Sudaryantiningsih; Agerippa Yanuranda Krismani; Widianto; Maria Yumima Banoet; Virgianto Tara Amah; John Tunggu Jama; Alfred Dedu Ngalung (PT FORMOSA CENDEKIA GLOBAL, 2022)
Currently, cases of hunger and malnutrition as indicators of food insecurity are common in developing countries. Based on the problems that occurred, a collaborative activity was carried out between the Environmental Engineering Study Program at Surakarta Christian University and PT. Bandungan Hydroponic Agrofarm (PT.HAB), and the Waluyo Panti Hospital Surakarta. The implementation of this Cooperation activity is carried out in 3 stages, namely: the preparation stage which includes selecting a topic, the stage for searching for activity participants and the stage for implementing activities in the form of training. One of the efforts that can be made to support the food security program, as well as improve the community's economy and the quality of the environment, especially the air in Surakarta City and other cities in Indonesia is by implementing a hydroponic farming system.